2012
DOI: 10.5301/jn.5000091
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 9 and vascular endothelial growth factor levels in human kidneys from lupus nephritis patients

Abstract: This is the first study that investigated combined expression of TLR9 and VEGF, which could be an important tool for understanding the role of TLR9 and VEGF in LN, with insights into the early detection and targeted treatment of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…In a study by Frieri et al, vascular endothelial growth factor (VEGF) expression in the renal tissues of eight LN patients was compared with a healthy control group. Their results showed a significant increase in VEGF expression in the LN group [21]. Similarly, Ding et al measured VEGF levels in 41 LN patients and found higher blood and urinary VEGF levels in the LN group [22].…”
Section: Discussionmentioning
confidence: 97%
“…In a study by Frieri et al, vascular endothelial growth factor (VEGF) expression in the renal tissues of eight LN patients was compared with a healthy control group. Their results showed a significant increase in VEGF expression in the LN group [21]. Similarly, Ding et al measured VEGF levels in 41 LN patients and found higher blood and urinary VEGF levels in the LN group [22].…”
Section: Discussionmentioning
confidence: 97%
“…NF-κB has a direct role with many different diseases such as sepsis, HIV [15,16] hypogammaglobulinemia [17], rhinosinusitis [18], rheumatoid arthritis, systemic lupus erythematosis [19], and lupus nephritis [20]. BTKdependent activation in hypogammaglobulinemia is related to NF-κB, essential for reprogramming the expression of genes that control B cell survival and proliferation [17] and D Pteronyssinusi-induced apoptosis-related rhinosinusitis can occur [18].…”
Section: Introductionmentioning
confidence: 99%
“…BTKdependent activation in hypogammaglobulinemia is related to NF-κB, essential for reprogramming the expression of genes that control B cell survival and proliferation [17] and D Pteronyssinusi-induced apoptosis-related rhinosinusitis can occur [18]. Toll-like receptor (TLR) can activate immune-mediated glomerulonephritis and VEGF levels in human kidneys from lupus nephritis patients [20]. The cytosolic domains of TLR recruit adaptor proteins and initiate signaling pathways in response to ligand binding and myeloid differentiation factor 88 (MyD88)-dependent pathway can lead to activation of the NF-B [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study including 20 patients suggested that vanin-1 level in peripheral blood may be a promissory biomarker for LN and warrants further validation in a larger cohort [70]. Other cytokines and chemokines have been proved to be associated with LN, including VEGF [71] and higher levels of IL-18 and IFNγ [72]. Increased levels of macrophage inflammatory protein-1α (CCL3), MCP-1, RANTES and IFNγ-induced protein-10 are also observed in the serum of SLE patients [73].…”
Section: Profiling Protein Biomarkers In Lnmentioning
confidence: 99%